A Metalinguistic Study on the Photon Interpretation Present in Physics Textbooks Approved in PNLDEM 2015: Elements for a Symmetric Sociology of Science Education (Revista Brasileira de Pesquisa em Educação em Ciências, 2018)
We present a work on Symmetric Sociology on Science Education from a theoretical framework that articulates Bruno Latour’s and Mikhail Bakhtin’s Philosophies. We perform a metalinguistic analysis of the texts about Quantum Physics present in the Physics textbook approved by the PNLDEM 2015 in dialogue with the philosophical interpretations about the photon in scientific papers. We present the dialogic relation among the different scientific and didactic speeches, explicating the re-elaboration of meaning that exists in every text. We show that the textbook authors hybridize different visions into a particular vision, which is not in dialogue with contemporary research in most textbooks, so these narratives could not even be considered Quantum Physics (since they attribute to photons a performance with many classical aspects). Furthermore, we show that all textbooks omit the theoretical construction that encompasses the photon, following the same didactic and ideological proposal found in undergraduate textbooks, as described by Kuhn, that is, omitting controversies and pushing the establishment of a paradigm. Such didactic parallel suggests the subordination of Science Education to the Scientific Community in a sort of didactic colonialism. Even if we agreed that the goal of Science Education is to educate “little scientists” (which is not the case), there is the problem that the paradigm presented by the texts has not been hegemonic for, at least, eight decades. Finally, the developed theoretical articulation proved to be fruitful to analyze Science Education and its symmetrical relations with nature and society.